Analisis Kewenangan Intelijen Kejaksaan Dalam Mengungkap Dugaan Tindak Pidana Korupsi Di Wilayah Hukum Kejaksaan Negeri Karanganyar - Lia Anggraeni Lia; Herwin Sulistyowati Herwin (Justicia Journal, 2024)
The Prosecutor's Intelligence has the sex of intelligence responsible for running the entire investigation chain, including the planning, collection, processing, and use of data, to maximize the results of the investigation. When a corruption crime is suspected or has occurred, data and information is collected and processed by the Prosecutor's Intelligence as part of the prosecution's efforts to uncover corruption crimes. At the investigation stage this task is carried out by the intelligence that exists at each stage of the prosecution position. The stage of investigation is carried out by the special criminal section which is given authority in the investigation of criminal offences, while in the stage of prosecution it is conducted by the Prosecutor General as stipulated in the regulations of the law – invitation. (1) What is the role of the Prosecutor's Intelligence in uncovering alleged corruption crimes? (2) Are the obstacles encountered by the Prosecutor's Intelligence in uncovering alleged criminal acts of corruption?The research approach used in this study is the Social Legal Approach conducted by studying the influence of law on social behavior. The location of the research was carried out at the Karanganyar State Prosecutor's Office located at Jl. Lawu No.361, Badran Asri, Cangakan, Kec. Data Collection Techniques (1) Interviews (2) Library is using Primary Data (1) Act No. 11 of 2021 on Amendments to Law No. 16 of 2004 on the Prosecutor's Office of the Republic of Indonesia; (2) Procurator's Regulations No. 6 of 2019 on Amending the Procedure Regulations of the Attorney-General No. PER-006/A/JA/07/2017 on the Organization and Working Rules of the Prosecution of the Republik of Indonesia (3) Act No.3 of 17 of 2011 on State Intelligence (4) Procuror-Governor's Ordinance No. Per-037 / A/JA/09/2011 of 23 September 2011 on the Operational Standards of Procedures (SOPs) of the Intelligence of the Ministry of Indonesia. Secondary data. Data analysis techniques with data analysis techniques used are qualitative analysis.The results of the research and the conclusion that (1) the Prosecutor's Intelligence played an important role in revealing the occurrence of corruption crimes. Before the case is brought into investigation, a network of intelligence activities is required to investigate whether or not there are indications of corruption offences that are detrimental to the state/region's finances. Successful disclosure of corruption crimes is in the hands of prosecutor's intelligence agents. The functions of the prosecution intelligence as the eye and ear of leadership, carrying out supporting in the implementation of all fields, as a source of information, data and support. In the course of the investigation, the intelligence agency performs activities such as Target Analysis, Task Analysis and Operation Target Determination to gather data and gather evidence that will serve as evidence that corruption crime has been committed that damages the state/region finances. Once the data and information are obtained, the intelligence agency of the Justice Intelligence Operation will conduct a more detailed investigation into the corruption crime. The information obtained is processed, analyzed and poured into reports of intelligence operations. If there are indications of corruption, the Intelligence Department will submit the report of the outcome of the judicial intelligence operation to the Special Criminal Prosecution Department for prosecution with the consent of the Chief Prosecutor of Karanganyar State. (2) Obstacles encountered by the Intelligence Branch of the State Prosecutor of Karanganyar in revealing the presence of corruption criminal acts, inter alia: (a) the time limit provided by the prosecutor's regulations; (b) in the Regulations of the Prosecution of the Republic of Indonesia there is no authority of Intelligence Agencies to undertake enforced efforts, so intelligence agents in the search for data must carry out disguise, slide or even steal the required data, this takes time related to the situation and circumstances; (c) Intelligence agents cannot guarantee that the outcomes of the Judicial Intelligence Operations referred to the Special Criminal Area go to the Corruption Penal Court, since the Intelligent Branch is only authorized to conduct investigations and bring the case to the special criminal area to carry out the investigation and prosecution; (d) the incidents or discovered have occurred over a very long time so that it is difficult to trace the existence of tools and evidence of the candidate suspect at the time of the suspension; (e) dealing with longer time due to lack of cooperation with the authorized authorities in the field